2015
DOI: 10.1042/bst20150125
|View full text |Cite
|
Sign up to set email alerts
|

Homology modelling of human P-glycoprotein

Abstract: P-glycoprotein (P-gp) is an ATP-binding cassette transporter that exports a huge range of compounds out of cells and is thus one of the key proteins in conferring multi-drug resistance in cancer. Understanding how it achieves such a broad specificity and the series of conformational changes that allow export to occur form major, on-going, research objectives around the world. Much of our knowledge to date has been derived from mutagenesis and assay data. However, in recent years, there has also been great prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
6
23
0
Order By: Relevance
“…Even in MD simulations, equilibrated models of murine P‐gp and its human homology model (obtained from 4Q9H, to be published by the authors) inserted in POPC bilayers adopt much smaller NBD distances very quickly (10–20 ns), ranging from 27.5 Å down to 24.6 Å, respectively. Other MD studies with human P‐gp homology models also showed that NBD–NBD distances rapidly evolve to similar distances (30–40 Å) when inserted in a lipid bilayer, independent of the distance registered in any of the murine templates (Table ) . From these computational models, additional insights on drug recognition and efflux mechanism were able to be obtained .…”
Section: New Mechanistic Insights From Structural Datamentioning
confidence: 84%
See 3 more Smart Citations
“…Even in MD simulations, equilibrated models of murine P‐gp and its human homology model (obtained from 4Q9H, to be published by the authors) inserted in POPC bilayers adopt much smaller NBD distances very quickly (10–20 ns), ranging from 27.5 Å down to 24.6 Å, respectively. Other MD studies with human P‐gp homology models also showed that NBD–NBD distances rapidly evolve to similar distances (30–40 Å) when inserted in a lipid bilayer, independent of the distance registered in any of the murine templates (Table ) . From these computational models, additional insights on drug recognition and efflux mechanism were able to be obtained .…”
Section: New Mechanistic Insights From Structural Datamentioning
confidence: 84%
“…Three generations of P‐gp modulators (inhibitors, Figure ) were developed, and many other molecules can be found in literature, which are reported to modulate P‐gp efflux . As P‐gp modulators are often structurally unrelated, it was initially thought that high log P values would be the major determinant for efflux modulation .…”
Section: Efflux Modulation: Past Present and Futurementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, tools are needed to understand in detail the role of these proteins in ML transport, and to consider them as relevant targets for reversion of AH resistance. The release of the 3D crystal structure of Cel-Pgp-1, with good resolution (Jin et al., 2012) and QMEAN Z-score (Domicevica and Biggin, 2015) provides an opportunity to launch a sound in silico structural study of drug binding to this protein. This is particularly relevant in the view of multispecific recognition, and hence expected transport capacity, of this model protein.…”
Section: Discussionmentioning
confidence: 99%